Devising an effective medical marketing strategy for a sustained customer engagement for a medical product organization (International Journal of Scientific Research and Management (IJSRM), 2017)
Protecting premium pricing is a challenge for pharmaceutical & medical device players in the global markets. With the global trend of making the healthcare services more affordable and more inclusive, this challenge continues to push us to create innovative strategies in marketing. Engagement of Healthcare Professionals through medical marketing strategies with appropriate planning and execution can lead to sustained value creation beyond product for which customers are more than willing to pay. This paper presents the planning and execution process of medical marketing strategies for enhanced customer engagement and improved business outcomes.